2010
DOI: 10.1128/jcm.01190-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Oseltamivir Resistance during Treatment of 2009 H1N1 Influenza Virus Infection in Immunocompromised Patients: Utility of Cycle Threshold Values of Qualitative Real-Time Reverse Transcriptase PCR

Abstract: Two immunocompromised patients with 2009 H1N1 influenza pneumonia had viral shedding for over 5 weeks despite therapy with oseltamivir. Declining or persistently low cycle threshold values noted on serial qualitative real-time reverse transcriptase PCR (rRT-PCR) of respiratory specimens implied increasing viral load and probable drug resistance. Oseltamivir resistance was later confirmed by pyrosequencing. CASE REPORTSCase report 1. A 52-year-old male with myelodysplastic syndrome underwent an allogeneic hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Such variability might have important implications in viral disease pathogenesis, and the study of viral genome evolution within a host can provide vital information important in developing and assessing antiviral agents [26]. For example, development of antiviral drug resistance during individualized therapy that is associated with poor outcome has been described extensively with influenza virus [27][28][29]. Grad et al reported intrahost genome evolution of respiratory syncytial virus over time in an infant with severe combined immune deficiency who underwent a bone marrow transplant [30].…”
Section: Discussionmentioning
confidence: 99%
“…Such variability might have important implications in viral disease pathogenesis, and the study of viral genome evolution within a host can provide vital information important in developing and assessing antiviral agents [26]. For example, development of antiviral drug resistance during individualized therapy that is associated with poor outcome has been described extensively with influenza virus [27][28][29]. Grad et al reported intrahost genome evolution of respiratory syncytial virus over time in an infant with severe combined immune deficiency who underwent a bone marrow transplant [30].…”
Section: Discussionmentioning
confidence: 99%
“…The samples with a high number of initial copies of target nucleic acid, are detected sooner and therefore they will have low values (usually around 20–25). However, those samples with very low numbers of copies are later detected, and the values are above 30–35 [5]. The sample is defined as positive when the analyzed by the qPCR technique is less than the established (threshold value).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid detection of oseltamivir resistance in severe pandemic H1N1 infections is essential for patients to receive maximum therapeutic benefit, and is useful for clinicians to allow for change to an effective treatment at a much earlier stage if resistance is found. Recent studies have reported the use of novel molecular methods to screen for the presence of the H275Y resistance mutation in the neuraminidase gene [58][59][60][61]. In addition to accurate detection of the H275Y oseltamivirresistance allele, samples collected at multiple time points even showed a switch from wild-type oseltamivir-sensitive 275 H to oseltamivir-resistant 275Y population after 9 days of treatment.…”
Section: Practical Importance Of Molecular Methods In Prompt Diagnosimentioning
confidence: 99%